2020
DOI: 10.1002/jpen.1993
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Phosphorus Intake by Parenteral Nutrition Prevents Metabolic Bone Disease of Prematurity in Extremely Low‐Birth‐Weight Infants

Abstract: Background Metabolic bone disease (MBD) is a common disorder in extremely low‐birth‐weight (ELBW) infants. However, no studies have investigated whether high‐dose calcium (Ca) and phosphorus (P) supplementation by parenteral nutrition (PN) prevents MBD in ELBW infants. This study aimed to identify the effect of PN on MBD in ELBW infants. Methods We retrospectively analyzed ELBW infants who were admitted between April 2011 and March 2017. ELBW infants were divided into the low‐P group (n = 22) and the high‐P gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It suggests that in the future use of parenteral nutrition for preterm infants, we should focus not only on duration, but also on the timing of the start of application as well as other aspects of details. Meanwhile, a Japanese study found that when preterm infants were given a high-phosphorus intake by parenteral nutritional, it guaranteed a high calcium intake, leading to a decrease in ALP levels in the first month ( 28 ). We suspect that the greater amount and better absorption of calcium and phosphorus in intravenous nutrition compared to oral supplementation might attenuate or delay the occurrence of MBDP.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that in the future use of parenteral nutrition for preterm infants, we should focus not only on duration, but also on the timing of the start of application as well as other aspects of details. Meanwhile, a Japanese study found that when preterm infants were given a high-phosphorus intake by parenteral nutritional, it guaranteed a high calcium intake, leading to a decrease in ALP levels in the first month ( 28 ). We suspect that the greater amount and better absorption of calcium and phosphorus in intravenous nutrition compared to oral supplementation might attenuate or delay the occurrence of MBDP.…”
Section: Discussionmentioning
confidence: 99%
“…OOP is associated with increased ventilator dependence and fractures in the short term, as well as abnormal bone development and poor growth in the long term. [5][6][7] Such morbidity can indirectly implicate OOP in increasing healthcare costs.…”
Section: Introductionmentioning
confidence: 99%